Voces para describir la seda en Constantinopla (Minerva. Revista de Filología Clásica, 2019)
This article focuses on Late Greek and Latin words describing silk garments and the silk itself. These terms are quite often an allusion to the dye of purple and its colour: blood. Since these are not technical words, but rather a description of a specific garment, an etymological interpretation is needed to understand words as alethinocrusta, holoverus, sericoblatta, etc.